Monetary Policy Autonomy and International Monetary Spillovers - Ishak Demir (University of Lincoln, Lincoln International Business School, Lincoln Economics and Finance Research Group (LEAF), 2019)
While Federal Reserve continues to normalize its monetary policy on the back of a strengthening U.S. economy, the possibility of mimicking U.S. policy actions and so the debate of monetary autonomy has been particularly heated in the most of developing countries, even in advanced economies. We analyse the role played by country-specific characteristics in domestic monetary policy autonomy to set short-term interest rates in the face of spillovers from of U.S. monetary policy as global external shocks. First, we extricate the non-systematic (non-autonomous) component of domestic interest rates which is related to business cycle synchronisation across countries. Then we employ an interacted panel VAR model, which allows impulse response functions to vary by country characteristics for a broad sample of countries. We find strong empirical evidence for the role of exchange rate flexibility, capital account openness in line with trilemma, but also a significant role for other country characteristics, such as dollarisation in the financial system, the presence of a global bank, use of macroprudential policies, and the credibility of fiscal and monetary policy.
Keywords: C38; E43; E52; E58; F42; G12; 330; monetary policy autonomy; global financial cycle; international spillovers; trilemma; country-specific characteristics; cross-country difference; dilemma